Study of steroid-resistant nephrotic syndrome: a single center experience - Youmna Ahmed Hassan Elbeltagi; Mahmoud Mohi El Din El Kersh; Hanan Mohammad Fathy; Nancy Abdel-Salam Kamel (SpringerOpen, 2024)
Abstract Background Nephrotic syndrome (NS) is a disease with favorable outcomes in most cases. Failure to respond to steroids is one of the most important predictors of clinical outcome. We performed a retrospective study on 51 primary idiopathic SRNS cases presenting between January 2011 and June 2021 at Alexandria University Children's Hospital (AUCH) by retrieving data from their clinic files. Cases with secondary causes of NS or suspected genetic causes were excluded from our study. Patients' demographic data, clinical and laboratory findings at the time of presentation, complications occurring during the course of treatment, immunosuppressants used along with steroids, and outcomes at the last follow-up were recorded. The mean duration of follow-up was 5.67 ± 3.07 years. Results Our results showed that there was male predominance (2.9:1), the mean age at first presentation was 4.53 ± 3.03 years, and persistent hematuria and systemic hypertension were found in 41.6% and 57.1%, respectively. The most common biopsy finding was MesPGN (37.3%). The most utilized immunosuppressant was cyclosporine (80.4%). Complete remission was fortunately the most prevalent outcome among our cases (52.2%). Conclusions Our study concluded that biopsy findings and thepresence of hematuria in SRNS cases are the most crucial factors in determining the final outcome. MCNS finding in biopsy is significantly correlated with complete remission (p value = 0.043). Persistent hematuria whether gross or microscopic was significantly correlated with unremitting disease (p value = 0.017).